ANALISIS FENOMENA UNDERPRICING SEBAGAI STRATEGI PADA PERUS-AHAAN GO PUBLIC DI INDONESIA - Diana, Patricia (Widya Mandala Surabaya Catholic University, 2022)
Research Purposes. This study aims to enrich findings about the underpricing phenomenon and to find underpricing trends in various economic conditions that affect stock market activity in the period of the year used in this study.Research Method. The underpricing phenomenon in this study was carried out in a reasonably long research period of 5 years from 2015 to 2019. A total of 72 companies were used as samples in the study. Data were analyzed using multiple regression analysis.Research Result and Findings. The results found that company size as measured by the number of company assets is the most significant factor for investors in determining their investment for companies that have just listed shares on the stock exchange. An assessment of a company's assets can be the basis for measuring risk, prospects, and the ability to provide returns in the future.